Learning and Innovation @ a Distance An Empirical Investigation into the Benefits and Liabilities of Different Forms of Distance on Interactive Learning and Novelty Creation in German Biotechnology SMEs - Hartig, Juliane; SpringerLink (Online service) (Wiesbaden : Gabler, 2011)
Firms of all sizes increasingly face the need to participate in global innovation cooperation. Yet, the global dimension adds another layer of complexity to open innovation processes. Juliane Hartig develops a framework for different forms of distance and discusses their impact and partial interplay for interactive learning and innovation. Her empirical study draws on a sample of international cooperation projects by small and medium-sized firms from the German biotechnology sector Combining quantitative and qualitative research, she provides new insights and offers practitioners tools for the creation of proximity in order to derive the most from global cooperation.
Keywords: Economics; Economics/Management Science; Innovation/Technology Management